All-weather anti-icing coating with composite photothermal and electrothermal properties and preparation method thereof
By using composite photothermal and electric-thermal properties anti-ice coating paint made of titanium carbide nanoparticles and other materials, the construction difficulty and performance stability problems in the field of anti-ice coating in the prior art are solved, and the all-weather efficient anti-ice, de-icing and self-cleaning functions are achieved.
Patent Information
- Application Number
- CN202411402236.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The prior art has problems such as cumbersome process, difficult construction, high energy consumption and safety hazards in the field of anti-ice coating, and the performance of the photothermal superhydrophobic coating is degraded under conditions such as nighttime, sand, dust, and low light.
All-weather anti-icing coating with composite photothermal and electric heating characteristics composed of titanium carbide nanoparticles, epoxy resin, stearic acid solution, ethyl orthosilicate, perfluorododecyl triethoxysilane, etc. is used to make it have efficient photothermal and electric heating conversion characteristics through ball milling and other processes.
The all-weather anti-icing, de-icing and self-cleaning functions are achieved. The light absorption rate of the coating in the 0.3~2.5μm solar band is higher than 97%, and the water contact angle on the surface is greater than 150°, which has excellent weather resistance and performance stability.
Smart Images

Figure CN119192948B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of solar thermal utilization, Joule heating and surface super-hydrophobic anti-icing coatings, and in particular to an all-weather anti-icing coating with composite photothermal and electrothermal properties and a preparation method thereof. Background Art
[0002] Under different altitudes and temperature and humidity conditions, the types of ice on the surface of objects can be divided into: rime, sleet, wet snow, fog and ice. Surface ice can seriously affect the operation and safe production of equipment. For example, the surface ice on the fan blades will not only increase the load on the fan blades and the main shaft, but also cause abnormal vibrations that will seriously affect the service life of the parts, and will also damage the aerodynamic performance of the blades, thereby reducing the output power of the unit. The power loss can even reach 60%; ice on the transmission line will cause the pantograph and contact network to take in the current unsmoothly, and in severe cases, it may even cause line interruption, seriously affecting the safety of the railway power supply system; ice on the wings of aircraft will seriously affect the flight status of the aircraft and the operation status of the engine, posing a huge hidden danger to the safety of passengers and crew members.
[0003] At present, compared with the traditional anti-icing and de-icing technology, which has the problems of complicated process, difficult construction, high energy consumption and various safety hazards, the coating and coating technology that uses super-hydrophobic properties and photothermal conversion to achieve rapid surface ice melting and de-icing has been widely developed. However, in the field of anti-icing, relying solely on photothermal super-hydrophobic coatings cannot meet the current application needs in the field of anti-icing and de-icing. This is because the photothermal super-hydrophobic coating is easily affected by the intensity of light radiation, which will cause water to nucleate and accumulate in the photothermal super-hydrophobic coating at night, in dust, weak light and other conditions. The "interlocking effect" of ice crystals between super-hydrophobic structures will cause the performance of the photothermal super-hydrophobic coating to decrease and fail. Therefore, giving the coating an efficient electrothermal Joule heating characteristic based on the photothermal super-hydrophobic coating is an ideal strategy to achieve outdoor all-weather anti-icing / de-icing functions.
[0004] CN 114656857A discloses an anti-icing material with multiple properties of photothermal and electrothermal conversion and wear-resistant super-hydrophobicity, as well as a preparation method and application thereof. The material coating is composed of an insulating layer, an electrode, and a photothermal, electrothermal, and super-hydrophobic layer arranged on a substrate layer. Under both electrothermal and photothermal conditions, the coating exhibits good thermal response characteristics and anti-icing properties. However, during the preparation process, the coating material not only requires additional conductive electrodes and insulating layers, but also requires the addition of nanoparticles with photothermal properties, nanoparticles with electrothermal properties, and nanoparticles with hydrophobic properties, which makes the coating material have a relatively complex preparation process and a high production cost. In addition, the curing temperature of the coating material is relatively high, which will increase the difficulty of construction under outdoor conditions and cause the material to be uncured or semi-cured, resulting in the failure of the coating material.
[0005] CN 111716776A discloses a photo-thermal super-hydrophobic film and a preparation method and an anti-icing and de-icing application. The film couples a functional particle material with photo-thermal and electro-thermal properties with PDMS, realizing the combination of photo-thermal de-icing, electro-thermal de-icing and super-hydrophobic anti-icing. However, the photo-thermal and electro-thermal properties of the film are realized under the secondary assembly method of the curing and spraying method, and the adhesion between the functional particles is weak, and there is a risk of functional failure under long-term wear conditions. In addition, the film uses the material cured by PDMS as a carrier. Under high temperature and extremely cold conditions, the anti-icing, de-icing and super-hydrophobic properties of the film will be affected by the flexibility of the film, which limits its application scenarios.
[0006] In addition, the commonly used anti-icing coatings are mainly based on two-dimensional materials of carbon and its allotropes, plasma nanoparticles or supersurfaces, black oxides, polymers, nitrides, MXene, high entropy alloys, etc. However, the high price, difficulty in dispersion, complex synthesis process, unstable performance and other defects limit the wide application of these materials.
[0007] Therefore, simple preparation process, economical raw materials, reasonable curing conditions, excellent weather resistance and performance stability are important breakthroughs in the development of anti-icing paints and coatings with composite photothermal and electrothermal properties. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide an all-weather anti-icing coating with composite photothermal and electrothermal properties, excellent weather resistance and stable performance.
[0009] Another technical problem to be solved by the present invention is to provide a method for preparing the all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0010] To solve the above problems, the present invention discloses an all-weather anti-icing coating with composite photothermal and electrothermal properties, characterized in that the coating is composed of the following raw materials in parts by weight: 10 to 30 parts of titanium carbide nanoparticles, 20 to 50 parts of epoxy resin, 1 to 5 parts of stearic acid solution, 1 to 5 parts of tetraethyl orthosilicate, 1 to 5 parts of 1H, 1H, 2H, 2H-perfluorododecyltriethoxysilane, 0.1 to 1 part of leveling agent, 0.1 to 1 part of dispersant, 0.1 to 1 part of defoaming agent, 0.1 to 1 part of curing agent, and 30 to 70 parts of solvent.
[0011] The titanium carbide nanoparticles are transition metal carbides with a particle size of 40-100 nm, a cubic crystal form, and a specific surface area of 20-65 m 2 / g, volume density is 0.15~0.56g / cm 3 .
[0012] The mass concentration of the stearic acid solution is 10-20 mmol / L.
[0013] The leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and EFKA 2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184.
[0014] The solvent is one or more of anhydrous ethanol, acetone and ethyl acetate.
[0015] The method for preparing the all-weather anti-icing coating with composite photothermal and electrothermal properties as described above comprises the following steps:
[0016] ⑴Weigh according to the ratio;
[0017] (2) Add titanium carbide nanoparticles, stearic acid solution, 1 / 2 of the total amount of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 3 / 5 of the total amount of the solvent, and stir at a speed of 800-1000 r / min for 60-100 min to obtain a mixed suspension component A;
[0018] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 400-500 r / min for 30-60 min to obtain a mixed suspension component B;
[0019] (4) Mix the mixed suspension component A with the mixed suspension component B, and add a leveling agent, a dispersant, a defoaming agent, and a curing agent in sequence, and ball mill them in a planetary ball mill for 120 to 160 minutes to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0020] In the step (4), the ball milling speed is 300-500 r / min.
[0021] The coating made of the all-weather anti-icing coating with composite photothermal and electrothermal properties as described above is characterized in that: the light absorption rate of the coating in the 0.3~2.5μm solar light band is greater than 97%, and the water contact angle on the coating surface is greater than 150°, and the water rolling angle on the coating surface is less than 5°.
[0022] The method for preparing the coating as described above comprises the following steps:
[0023] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0024] Step 2: The etched substrate surface is ultrasonically cleaned for 30 to 60 minutes and then dried to obtain a treated substrate surface;
[0025] Step 3: Fill the all-weather anti-icing coating with composite photothermal and electrothermal properties into a 1.5 mm caliber spray gun, and spray the coating on the treated substrate surface by a spraying method to obtain a wet film with a thickness of 120-160 μm;
[0026] Step 4: Curing the wet film at room temperature for 24 hours or in a muffle furnace at 90° C. for 3 to 4 hours to obtain a dry film with a thickness of 50 to 80 μm.
[0027] The spraying conditions in step 3 are as follows: the spraying environment temperature is 15-30° C., the relative air humidity is 35-85%, the spraying pressure is 0.3-0.4 MPa, the spraying speed is 2-2.5 m / min, and the spraying times are twice.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] 1. The present invention uses transition metal carbide titanium carbide as the main functional filler, with a particle size of 40-100 nm, a crystal form of NaCl-type cubic structure, and a specific surface area of 20-65 m 2 / g, and the bulk density is 0.15~0.56 g / cm 3 . Titanium carbide nanoparticles have high melting point, high hardness, high Young's modulus, high chemical stability, wear resistance and corrosion resistance. At the same time, with good electrical and thermal conductivity, titanium carbide nanoparticles can be used as conductive materials to generate Joule heat, and then achieve anti-icing performance on the surface through two-way heat transfer between particles. On the other hand, titanium carbide nanoparticles can be effectively used in photothermal conversion applications due to their unique d-band electronic structure and plasma resonance, which will lead to rapid local heating of their surface. Compared with traditional photothermal materials such as gold nanoparticles, carbon nanotubes and graphene oxide, titanium carbide nanoparticles are easier to disperse in coatings and have a wider absorption spectrum. The characteristic that its spectral range extends to the near-infrared region is more suitable for applications in the field of anti-icing.
[0030] 2. The titanium carbide nanoparticles used in the present invention have excellent photothermal and electrothermal composite properties, are easy to disperse in the coating and do not require the addition of additional photothermal or electrothermal functional particles, making the production and processing of the coating more cost-effective and environmentally friendly.
[0031] 3. The ethyl orthosilicate added in the present invention provides a large number of hydrolyzed Si-O groups on the surface of the titanium carbide nanoparticles, so that the surface can be grafted with the low surface energy groups in 1H,1H,2H,2H-perfluorododecyltriethoxysilane, thereby achieving low surface energy treatment of the particles and providing a structural basis for the superhydrophobic properties of the coating.
[0032] 4. The curing agent added in the present invention can, on the one hand, undergo a condensation reaction with titanium carbide nanoparticles having Si-O groups on the surface to enhance the adhesion and compactness between the particles, so that the continuous phase of titanium carbide nanoparticles in the coating prepared by the coating maintains good electrical conductivity, thermal conductivity and Joule heating properties. On the other hand, it can couple with the substrate to enhance the adhesion between the coating and the substrate, and improve the mechanical, water erosion resistance, wear resistance, and aging resistance properties of the coating.
[0033] 5. The coating made of the all-weather anti-icing coating with the composite photothermal and electrothermal characteristics of the present invention has a light absorption rate of more than 97% in the 0.3~2.5μm solar light band. The reasons for the ultra-high light absorption characteristics of the coating surface are mainly as follows:
[0034] ①Intrinsic absorption characteristics of titanium carbide nanoparticles.
[0035] ② During the curing process of the coating on the substrate, a structural characteristic with micropores and micro-skeleton is formed. Such a structure enhances the light capture ability of the surface and prolongs the propagation path of light. Multiple reflections of light enhance the light absorption characteristics of the surface.
[0036] ③ Under the action of epoxy resin, curing agent and ethyl orthosilicate, titanium carbide nanoparticles adhere to each other to form a secondary microstructure at the micrometer and nanometer levels. This structure also extends the propagation path of light and enhances the light absorption characteristics of the surface.
[0037] 6. The coating made of the all-weather anti-icing coating with the composite photothermal and electrothermal properties of the present invention has the coupling characteristics of super-hydrophobicity, photothermal conversion and electrothermal conversion. The coating is not affected by lighting conditions and can achieve all-weather surface anti-icing, defrosting, self-cleaning and anti-fouling properties. The water contact angle on the coating surface exceeds 150°, and the water sliding angle is <5°. In an extremely cold environment of -60°C, the droplets on the coating surface are irradiated by standard sunlight and a low power density (0.2W / cm 2 ) still has anti-condensation properties, such as Figure 6 shown.
[0038] 7. The coating made of the all-weather anti-icing coating with composite photothermal and electrothermal properties of the present invention has strong weather resistance and performance stability in corrosive and abrasive environments: after the coating is immersed in 1 mol / L acid, alkali and salt solution for 72 hours, the super-hydrophobic and photothermal coupling properties of the coating surface are still maintained; after the coating is rubbed on 800-mesh sandpaper for 10 m at a pressure of 2.5 kPa, the contact angle of the surface is still higher than 150°, and its super-hydrophobic properties are maintained; when the coating is in an actual application environment, under clear weather conditions during the day, the coating surface (25 cm 2 ) is about 22℃ higher than the average temperature of the surrounding environment; at night without light, the coating surface (25cm 2 ) is only 0.04 W / cm 2 At an ultra-low power density, the average surface temperature can be 2.6°C higher than the average ambient temperature; when the coating undergoes corrosion, wear and other tests, its light absorption rate is still over 93%, ensuring the weather resistance of the coating's photothermal anti-icing properties. Figures 8-10 shown.
[0039] 8. The present invention is simple to operate, has high production efficiency, does not require complicated processing procedures, can be matched with a variety of substrates (copper, stainless steel, etc.), has a dense coating surface, and has no blistering, cracking, etc. It can be widely used in aviation and navigation, wind power generation, power transmission, chemical industry, seawater desalination, agricultural equipment and other fields in cold environments for anti-icing and deicing needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0041] Figure 1 This is a diagram of the superhydrophobic properties of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 1 of the present invention.
[0042] Figure 2 The icing delay diagram of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 2 of the present invention and the uncoated substrate.
[0043] Figure 3 The temperature rise diagram of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 3 of the present invention at different power densities.
[0044] Figure 4 The all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 3 of the present invention and the uncoated substrate have an average thermal conductivity of 0.2 W / cm 2 Diagram of the defrost process under power density.
[0045] Figure 5The all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 4 of the present invention is heated to 1 kw / m 2 Diagram of the deicing process under lighting conditions.
[0046] Figure 6 This is an anti-icing diagram of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 4 of the present invention under extremely cold conditions.
[0047] Figure 7 These are the appearance graphs of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 4 of the present invention after being immersed in 1 mol / L acid, alkali and salt solutions for 72 hours respectively.
[0048] Figure 8 This is a diagram of the wetting characteristics of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 5 of the present invention at different wear distances.
[0049] Fig. 9 This is a temperature variation diagram during the day and night for the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 5 of the present invention.
[0050] Fig.10 Light absorption spectrum of the surface of the all-weather anti-icing coating with composite photothermal and electrothermal properties prepared in Example 5 of the present invention after being subjected to acid, alkali, and salt corrosion tests, sandpaper wear tests, and falling sand wear tests. DETAILED DESCRIPTION
[0051] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials in parts by weight (g): 10-30 parts of titanium carbide nanoparticles, 20-50 parts of epoxy resin, 1-5 parts of stearic acid solution, 1-5 parts of tetraethyl orthosilicate, 1-5 parts of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.1-1 parts of leveling agent, 0.1-1 parts of dispersant, 0.1-1 parts of defoaming agent, 0.1-1 parts of curing agent, and 30-70 parts of solvent.
[0052] Among them: Titanium carbide nanoparticles are transition metal carbides with a particle size of 40~100nm, a cubic crystal form, and a specific surface area of 20~65m 2 / g, volume density is 0.15~0.56g / cm 3 .
[0053] The mass concentration of stearic acid solution is 10~20 mmol / L.
[0054] The leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and Efka EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and Efka EFKA2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184.
[0055] The solvent is one or more of anhydrous ethanol, acetone and ethyl acetate.
[0056] The preparation method of the all-weather anti-icing coating with composite photothermal and electrothermal properties comprises the following steps:
[0057] ⑴Weigh according to the ratio;
[0058] (2) Add titanium carbide nanoparticles, stearic acid solution, 1 / 2 of the total amount of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 3 / 5 of the total amount of the solvent, and stir at a speed of 800-1000 r / min for 60-100 min to obtain a mixed suspension component A;
[0059] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 400-500 r / min for 30-60 min to obtain a mixed suspension component B;
[0060] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill them in a planetary ball mill at a speed of 300-500 r / min for 120-160 min to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0061] The coating made of the all-weather anti-icing coating with composite photothermal and electrothermal properties has a light absorption rate of >97% in the 0.3~2.5μm solar light band, a water contact angle on the coating surface of >150°, and a water rolling angle on the coating surface of <5°.
[0062] The method for preparing the coating comprises the following steps:
[0063] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm; the substrate is copper, stainless steel, etc.;
[0064] Step 2: The etched substrate surface is ultrasonically cleaned for 30 to 60 minutes and then dried to obtain a treated substrate surface;
[0065] Step 3: Fill the all-weather anti-icing coating with composite photothermal and electrothermal properties into a 1.5mm caliber spray gun, and spray the coating on the treated substrate surface by spraying. The spraying environment temperature is 15-30°C, the relative air humidity is 35-85%, the spraying pressure is 0.3-0.4MPa, the spraying speed is 2-2.5m / min, and the number of spraying is twice, so as to obtain a wet film with a thickness of 120-160μm;
[0066] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 50-80 μm.
[0067] Example 1
[0068] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials: 10g of titanium carbide nanoparticles, 20g of epoxy resin, 1g of stearic acid solution, 1g of tetraethyl orthosilicate, 1g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.1g of leveling agent, 0.1g of dispersant, 0.1g of defoaming agent, 0.1g of curing agent, and 30g of solvent.
[0069] Among them: the particle size of titanium carbide nanoparticles is 40 nm, the crystal form is cubic, and the specific surface area is 65m 2 / g, volume density is 0.15 g / cm 3 .
[0070] The mass concentration of stearic acid solution is 10 mmol / L.
[0071] The leveling agent is Digo Glide 450 silicone leveling agent; the dispersant is Digo TEGO755W; the defoaming agent is Digo TEGO 901W polyether siloxane defoaming agent; and the curing agent is KH550.
[0072] The solvent is anhydrous ethanol.
[0073] The preparation method thereof comprises the following steps:
[0074] ⑴Weigh according to the ratio;
[0075] (2) Add titanium carbide nanoparticles, stearic acid solution, 0.5 g of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 18 g of solvent, and stir at a speed of 800 r / min for 60 min to obtain a mixed suspension component A;
[0076] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 400 r / min for 30 min to obtain a mixed suspension component B;
[0077] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill for 120 min at a speed of 300 r / min in a planetary ball mill to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0078] The method for preparing the coating comprises the following steps:
[0079] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0080] Step 2: The etched substrate surface is ultrasonically cleaned for 30 minutes and then dried to obtain a treated substrate surface;
[0081] Step 3: 10g of the all-weather anti-icing coating with composite photothermal and electrothermal properties is filled into a 1.5mm caliber spray gun, and the coating is sprayed on the treated substrate surface by spraying. The spraying environment temperature is 15°C, the relative air humidity is 85%, the spraying pressure is 0.3MPa, the spraying speed is 2.5 m / min, and the number of spraying is twice, so as to obtain a wet film with a thickness of 120μm;
[0082] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 50 μm.
[0083] The solar absorptivity of the coating was evaluated using a Lambda 950 UV / visible / near-infrared spectrophotometer (equipped with a 150 mm integrating sphere) manufactured by PerkinElmer, USA, and its absorptivity in the 0.3-2.5 μm band was measured. The solar absorptivity was then calculated according to the calculation formula in the international standard ISO 9845-1 (1992). The solar absorptivity of the coating prepared in Example 1 in the 0.3-2.5 μm band was measured to be 0.973.
[0084] The water contact angle and water sliding angle of the surface were characterized by an angular contact meter (JY-PHb). The volume of the test water droplet was 10 μL. The water contact angle of the coating prepared in Example 1 was measured to be 157°, and the water sliding angle was 3.8°.
[0085] Figure 1 The superhydrophobic property diagram of the prepared coating shows that the coating surface has superhydrophobicity, self-cleaning, antifouling and self-cleaning properties.
[0086] Example 2
[0087] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials: 15g of titanium carbide nanoparticles, 25g of epoxy resin, 2g of stearic acid solution, 2g of tetraethyl orthosilicate, 1.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.2g of leveling agent, 0.2g of dispersant, 0.15g of defoaming agent, 0.25g of curing agent, and 30g of solvent.
[0088] Among them: the particle size of titanium carbide nanoparticles is 40 nm, the crystal form is cubic, and the specific surface area is 65 m 2 / g, volume density is 0.15 g / cm 3 .
[0089] The mass concentration of stearic acid solution is 10 mmol / L.
[0090] The leveling agent is AFCONA 3777 fluorocarbon modified polyacrylate leveling agent; the dispersant is TEGO 662 C; the defoamer is EFKA 2720 unsaturated polyester defoamer; and the curing agent is KH550.
[0091] The solvent is acetone.
[0092] The preparation method thereof comprises the following steps:
[0093] ⑴Weigh according to the ratio;
[0094] (2) Add titanium carbide nanoparticles, stearic acid solution, 1 g of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 18 g of solvent, and stir at a speed of 800 r / min for 80 min to obtain a mixed suspension component A;
[0095] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 400 r / min for 30 min to obtain a mixed suspension component B;
[0096] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill for 120 min at a speed of 300 r / min in a planetary ball mill to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0097] The method for preparing the coating comprises the following steps:
[0098] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0099] Step 2: The etched substrate surface is ultrasonically cleaned for 45 minutes and then dried to obtain a treated substrate surface;
[0100] Step 3: 10g of the all-weather anti-icing coating with composite photothermal and electrothermal properties was filled into a 1.5mm caliber spray gun, and the coating was sprayed on the treated substrate surface by spraying. The spraying environment temperature was 20°C, the relative air humidity was 72%, the spraying pressure was 0.35MPa, the spraying speed was 2 m / min, and the number of spraying was twice, so as to obtain a wet film with a thickness of 138μm.
[0101] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 68 μm.
[0102] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 2 in the 0.3-2.5 μm band was measured to be 0.982, the water contact angle was 156.3°, and the water sliding angle was 4.3°.
[0103] Figure 2 The figure shows the comparison of ice formation delay between the coated surface (PESHS) and the uncoated surface (Untreated) under lightless and high humidity conditions, indicating that the coating has good passive anti-icing performance.
[0104] Example 3
[0105] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials: 15g of titanium carbide nanoparticles, 25g of epoxy resin, 2.5g of stearic acid solution, 3g of tetraethyl orthosilicate, 2.5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.2g of leveling agent, 0.2g of dispersant, 0.15g of defoaming agent, 0.25g of curing agent, and 50g of solvent.
[0106] Among them: the particle size of titanium carbide nanoparticles is 50 nm, the crystal form is cubic, and the specific surface area is 38.7 m 2 / g, volume density is 0.28 g / cm 3 .
[0107] The mass concentration of stearic acid solution is 15 mmol / L.
[0108] The leveling agent is AFCONA 3034; the dispersant is EFKA 5065; the defoaming agent is TEGO 901W polyether siloxane defoaming agent and EFKA 2720 unsaturated polyester defoaming agent (1:1); the curing agent is KH550.
[0109] The solvent was ethyl acetate.
[0110] The preparation method thereof comprises the following steps:
[0111] ⑴Weigh according to the ratio;
[0112] (2) Add titanium carbide nanoparticles, stearic acid solution, 1.5 g of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 30 g of solvent, and stir at a speed of 800 r / min for 80 min to obtain a mixed suspension component A;
[0113] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 500 r / min for 30 min to obtain a mixed suspension component B;
[0114] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill for 120 min at a speed of 500 r / min in a planetary ball mill to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0115] The method for preparing the coating comprises the following steps:
[0116] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0117] Step 2: The etched substrate surface is ultrasonically cleaned for 45 minutes and then dried to obtain a treated substrate surface;
[0118] Step 3: 10g of the all-weather anti-icing coating with composite photothermal and electrothermal properties was filled into a 1.5mm caliber spray gun, and the coating was sprayed on the treated substrate surface by spraying. The spraying environment temperature was 25°C, the relative air humidity was 58%, the spraying pressure was 0.35MPa, the spraying speed was 2 m / min, and the number of spraying was twice, so as to obtain a wet film with a thickness of 144μm.
[0119] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 73 μm.
[0120] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 3 in the 0.3-2.5 μm band was measured to be 0.985, the water contact angle was 157.4°, and the water sliding angle was 3.6°.
[0121] Figure 3 The surface temperature rise curve of the prepared coating at different power densities shows that the coating has excellent Joule heating effect and adjustable surface temperature control properties.
[0122] Figure 4 The prepared coating is at 0.2 W / cm 2 The defrosting process of coated and uncoated surfaces under power density conditions. The results show that the electrothermal and superhydrophobic coupling properties of the coating can greatly improve the anti-icing and deicing performance of the surface.
[0123] Example 4
[0124] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials: 20g of titanium carbide nanoparticles, 40g of epoxy resin, 3.5g of stearic acid solution, 4g of tetraethyl orthosilicate, 5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.5g of leveling agent, 0.5g of dispersant, 0.8g of defoaming agent, 0.8g of curing agent, and 60g of solvent.
[0125] Among them: the particle size of titanium carbide nanoparticles is 80 nm, the crystal form is cubic, and the specific surface area is 32 m 2 / g, volume density is 0.41 g / cm 3 .
[0126] The mass concentration of stearic acid solution is 20 mmol / L.
[0127] The leveling agent is AFCONA 3034; the dispersant is EFKA 5065; the defoamer is TEGO901W polyether siloxane defoamer; and the curing agent is KH550 and SYLGARD (1:1).
[0128] The solvent is anhydrous ethanol and ethyl acetate (mass ratio is 1:1).
[0129] The preparation method thereof comprises the following steps:
[0130] ⑴Weigh according to the ratio;
[0131] (2) Add titanium carbide nanoparticles, stearic acid solution, 2 g of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 36 g of solvent, and stir at a speed of 1000 r / min for 80 min to obtain a mixed suspension component A;
[0132] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 500 r / min for 30 min to obtain a mixed suspension component B;
[0133] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill for 140 min at a speed of 500 r / min in a planetary ball mill to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0134] The method for preparing the coating comprises the following steps:
[0135] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0136] Step 2: The etched substrate surface is ultrasonically cleaned for 30 minutes and then dried to obtain a treated substrate surface;
[0137] Step 3: 10g of the all-weather anti-icing coating with composite photothermal and electrothermal properties was filled into a 1.5mm caliber spray gun, and the coating was sprayed on the treated substrate surface by spraying. The spraying environment temperature was 23°C, the relative air humidity was 65%, the spraying pressure was 0.4MPa, the spraying speed was 2.5m / min, and the number of spraying was twice, so as to obtain a wet film with a thickness of 132μm.
[0138] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 73 μm.
[0139] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 4 in the 0.3-2.5 μm band was measured to be 0.979, the water contact angle was 156.8°, and the water sliding angle was 3.9°.
[0140] Figure 5 Indicated at 1kW / m 2The photothermal deicing comparison diagram between the coating prepared by the coating and the substrate without coating under the illumination condition of . The results show that the photothermal characteristics of the coating and the superhydrophobic coupling characteristics can greatly improve the anti-icing and deicing performance of the surface, and avoid the pinning effect of the traditional superhydrophobic anti-icing surface under low temperature and high humidity conditions.
[0141] Figure 6 It means that the prepared coating has a power of 1kW / m 2 The light power and 0.2W / cm 2 The anti-icing diagram of water droplets on the coating surface under power density conditions. The results show that under the coupling of electrothermal and photothermal effects, the temperature difference between the water droplets and the surface exceeds 60°C and remains uncondensed, indicating that in an extremely cold environment of -60°C, the droplets on the coating surface still have anti-condensation properties.
[0142] Figure 7 The surface of the prepared coating was immersed in 1 mol / L acid, alkali and salt solutions for 72 hours. The figure shows that there is no obvious change or reaction on the surface of the coating after long-term immersion, indicating that the coating has excellent physical barrier and chemical passivity.
[0143] Example 5
[0144] An all-weather anti-icing coating with composite photothermal and electrothermal properties, the coating is composed of the following raw materials: 30g of titanium carbide nanoparticles, 50g of epoxy resin, 5g of stearic acid solution, 5g of tetraethyl orthosilicate, 5g of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 1.0g of leveling agent, 1.0g of dispersant, 1.0g of defoaming agent, 1.0g of curing agent, and 70g of solvent.
[0145] Among them: the particle size of titanium carbide nanoparticles is 100nm, the crystal form is cubic, and the specific surface area is 20m 2 / g, volume density is 0.56g / cm 3 .
[0146] The mass concentration of stearic acid solution is 20 mmol / L.
[0147] The leveling agent is AFCONA 3777 fluorocarbon modified polyacrylate; the dispersant is TEGO755W; the defoamer is EFKA 2720 unsaturated polyester defoamer; and the curing agent is SYLGARD 184.
[0148] The solvent was ethyl acetate.
[0149] The preparation method thereof comprises the following steps:
[0150] ⑴Weigh according to the ratio;
[0151] (2) Add titanium carbide nanoparticles, stearic acid solution, 2.5 g of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 42 g of solvent, and stir at a speed of 1000 r / min for 100 min to obtain a mixed suspension component A;
[0152] ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 500 r / min for 30 min to obtain a mixed suspension component B;
[0153] (4) Mix the mixed suspension component A with the mixed suspension component B, and add the leveling agent, dispersant, defoaming agent and curing agent in sequence, and ball mill for 160 min at a speed of 500 r / min in a planetary ball mill to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
[0154] The method for preparing the coating comprises the following steps:
[0155] Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm;
[0156] Step 2: The etched substrate surface is ultrasonically cleaned for 60 minutes and then dried to obtain a treated substrate surface;
[0157] Step 3: 10 g of the all-weather anti-icing coating with composite photothermal and electrothermal properties was filled into a 1.5 mm caliber spray gun, and the coating was sprayed on the treated substrate surface by spraying. The spraying environment temperature was 30 ° C, the relative air humidity was 35%, the spraying pressure was 0.4 MPa, the spraying speed was 2 m / min, and the number of spraying was twice, so as to obtain a wet film with a thickness of 160 μm;
[0158] Step 4: Cure the wet film at room temperature for 24 hours or in a muffle furnace at 90°C for 3-4 hours to obtain a dry film with a thickness of 80 μm.
[0159] The absorptivity, water contact angle and water sliding angle tests of the prepared coating in the 0.3-2.5 μm band were the same as those in Example 1. The solar absorptivity of the coating prepared in Example 5 in the 0.3-2.5 μm band was measured to be 0.975, the water contact angle was 155.4°, and the water sliding angle was 4.4°.
[0160] Figure 8 The wettability change diagram of the prepared coating after different friction distances on 800 mesh gauze paper under 2.5 kPa pressure. The results show that after the coating is rubbed on sandpaper for 10 m, the water contact angle on its surface is still higher than 150°, indicating that the superhydrophobic properties of the coating are maintained and it has good wear resistance.
[0161] Fig. 9 The temperature rise diagram of the prepared coating surface (PESHS) and the surrounding environment under sunny day conditions in the actual application environment; when the power density is only 0.04 W / cm 2 The temperature rise diagram of the coating surface (PESHS) and the surrounding environment under no light conditions at night (the black line in the figure is the actual ambient temperature, and the yellow line is the coating surface temperature). The results show that under clear weather conditions, the coating surface (25cm 2 ) is about 22℃ higher than the average temperature of the surrounding environment; at night without light, the coating surface (25cm 2 ) at 0.04 W / cm 2 The average temperature at ultra-low power density is about 2.6°C higher than the average temperature of the surrounding environment. This shows that the prepared coating surface is not restricted by weather and light conditions, and achieves all-weather, adjustable and fast-response passive anti-icing and active deicing performance requirements under super-hydrophobic, photothermal and electrothermal coupling characteristics.
[0162] Fig.10 The light absorption spectrum of the prepared coating surface after acid, alkali, salt corrosion test, sandpaper wear and falling sand wear test. The results show that when the coating undergoes corrosion and wear tests, its light absorption rate is still over 93%, ensuring the weather resistance of the coating's light and thermal properties and anti-icing and de-icing properties.
[0163] In summary, the coating formed by the all-weather anti-icing coating with composite photothermal and electrothermal properties obtained in Examples 1 to 5 has a solar absorptivity of more than 0.97 in the 0.3 to 2.5 μm band and has good superhydrophobic properties. Due to the photothermal conversion, Joule heating and superhydrophobic coupling characteristics of the coating, the coating has rapid anti-icing and defrosting properties, and still has anti-icing properties under extremely cold conditions of -60°C. The coating also has excellent performance stability and weather resistance, which provides conditions for the all-weather anti-icing application of the coating in extreme and complex environments.
[0164] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. All changes made within the scope of protection of the independent claims of the present invention are within the scope of protection of the present invention.
Claims
1. An all-weather anti-icing coating with composite photothermal and electrothermal properties, characterized by: The coating is composed of the following raw materials in parts by weight: 10-30 parts of titanium carbide nanoparticles, 20-50 parts of epoxy resin, 1-5 parts of stearic acid solution, 1-5 parts of ethyl orthosilicate, 1-5 parts of 1H,1H,2H,2H-perfluorododecyltriethoxysilane, 0.1-1 parts of leveling agent, 0.1-1 parts of dispersant, 0.1-1 parts of defoamer, 0.1-1 parts of curing agent, and 30-70 parts of solvent; the titanium carbide nanoparticles are transition metal carbides, with a particle size of 40-100 nm, a cubic crystal form, and a specific surface area of 20-65 m 2 / g, volume density is 0.15~0.56g / cm 3 ; The mass concentration of the stearic acid solution is 10-20 mmol / L; the leveling agent is one or two of Digo Glide 450 silicone leveling agent, AFCONA 3777 fluorocarbon modified polyacrylate leveling agent, and AFCONA 3034 leveling agent; the dispersant is one or two of Digo TEGO755W, Digo TEGO 662 C, and EFKA 5065; the defoamer is one or two of Digo TEGO 901W polyether siloxane defoamer and EFKA 2720 unsaturated polyester defoamer; the curing agent is one or two of KH550 and SYLGARD 184; the solvent is one or more of anhydrous ethanol, acetone, and ethyl acetate.
2. The method for preparing the all-weather anti-icing coating with composite photothermal and electrothermal properties as claimed in claim 1 comprises the following steps: ⑴Weigh according to the ratio; (2) Add titanium carbide nanoparticles, stearic acid solution, 1 / 2 of the total amount of ethyl orthosilicate, and 1H,1H,2H,2H-perfluorododecyltriethoxysilane to 3 / 5 of the total amount of the solvent, and stir at a speed of 800-1000 r / min for 60-100 min to obtain a mixed suspension component A; ⑶ Add epoxy resin and remaining ethyl orthosilicate to the remaining solvent, and stir at a speed of 400-500 r / min for 30-60 min to obtain a mixed suspension component B; (4) Mix the mixed suspension component A with the mixed suspension component B, and add a leveling agent, a dispersant, a defoaming agent, and a curing agent in sequence, and ball mill them in a planetary ball mill for 120 to 160 minutes to obtain an all-weather anti-icing coating with composite photothermal and electrothermal properties.
3. The method for preparing an all-weather anti-icing coating with composite photothermal and electrothermal properties as claimed in claim 2, characterized in that: In the step (4), the ball milling speed is 300-500 r / min.
4. A coating made of an all-weather anti-icing coating with composite photothermal and electrothermal properties as claimed in claim 1, characterized in that: The light absorption rate of the coating in the 0.3~2.5μm solar light band is greater than 97%, and the water contact angle on the coating surface is greater than 150°, and the water rolling angle on the coating surface is less than 5°.
5. The method for preparing the coating according to claim 4, comprising the following steps: Step 1: electrochemically etch the substrate surface using electrochemical processing equipment to form a uniformly distributed micro-pit structure on the substrate surface with a surface roughness of 25-100 μm; Step 2: The etched substrate surface is ultrasonically cleaned for 30 to 60 minutes and then dried to obtain a treated substrate surface; Step 3: Fill the all-weather anti-icing coating with composite photothermal and electrothermal properties described in claim 1 into a 1.5 mm caliber spray gun, and spray the coating on the treated substrate surface by spraying to obtain a wet film with a thickness of 120-160 μm; Step 4: Curing the wet film at room temperature for 24 hours or in a muffle furnace at 90° C. for 3 to 4 hours to obtain a dry film with a thickness of 50 to 80 μm.
6. The method for preparing the coating according to claim 5, characterized in that: The spraying conditions in step 3 are as follows: the spraying environment temperature is 15-30° C., the relative air humidity is 35-85%, the spraying pressure is 0.3-0.4 MPa, the spraying speed is 2-2.5 m / min, and the spraying times are twice.
Citation Information
Patent Citations
Photoelectric-thermal superhydrophobic film, preparation method thereof and anti-icing and deicing application
CN111716776A
Anti-icing material with electrothermal photothermal conversion capability and wear-resistant and super-hydrophobic multiple properties as well as preparation method and application of anti-icing material
CN114656857A
Super-hydrophobic coating with photo-thermal deicing and long-acting corrosion resistance and preparation method
CN115044297A